Progress in the development of small molecular inhibitors of the Bruton's tyrosine kinase (BTK) as a promising cancer therapy. (1st October 2021) - Liu, Xiu-Juan; Xu-Liu,; Pang, Xiao-Jing; -Ying Yuan, Xin; Yu, Guang-Xi; Li, Yin-Ru; Guan, Yong-Feng; Zhang, Yan-Bing; Song, Jian; Zhang, Qiu-Rong; Zhang, Sai-Yang
Graphical abstract: Abstract: Bruton tyrosine kinase (BTK) is a key kinase in the B cell antigen receptor signal transduction pathway, which is involved in the regulation of the proliferation, differentiation and apoptosis of B cells. BTK has become a significant target for the treatment of hematological malignancies and autoimmune diseases. Ibrutinib, the first-generation BTK inhibitor, has made a great contribution to the treatment of B cell malignant tumors, but there are still some problems such as resistance or miss target of site mutation. Therefore, there is an imperative need to develop novel BTK inhibitors to overcome these problems. Besides, proteolysis targeting chimera (PROTAC) technology has been successfully applied to the development of BTK degradation agents, which has opened a fresh way for the BTK targeted treatment. This paper reviews the biological function of BTK, the discovery and development of BTK targeted drugs as a promising cancer therapy. It mainly reviews the binding sites and structural characteristics of BTK, structure–activity relationships, activity and drug resistance of BTK inhibitors, as well as potential treatment strategies to overcome the resistance of BTK, which provides a reference for the rational design and development of new powerful BTK inhibitors.